2007
DOI: 10.1002/elps.200700168
|View full text |Cite
|
Sign up to set email alerts
|

Effect of detergent on electromigration of proteins: CE of very low density lipoprotein receptor modules and viral proteins

Abstract: The different electrophoretic behavior of the members of two groups of proteins with respect to the absence or presence of detergent additives in the BGE was explored. Recombinant soluble concatemers of repeat 3 of the very low density lipoprotein (VLDL)-receptor fused at their N-terminus to maltose-binding protein (MBP) exhibited different electrophoretic mobilities in borate buffer (pH 8.3) in the absence and in the presence of dodecyl-PEG ether (D-PEG). This enabled the separation of the receptor fragments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…This corresponded to the three triazines and CBZ, but with no separation (a complete loss of resolution). This type of behaviour is similar to that reported by Kenndler and co‐workers 38, 39 for the electrophoretic separation of proteins with SDS in the sample zone, not in the BGE. Those authors suggested that the system was behaving as an unintentional‐isotachophoresis system under conditions aimed at carrying out zone electrophoresis.…”
Section: Resultssupporting
confidence: 90%
“…This corresponded to the three triazines and CBZ, but with no separation (a complete loss of resolution). This type of behaviour is similar to that reported by Kenndler and co‐workers 38, 39 for the electrophoretic separation of proteins with SDS in the sample zone, not in the BGE. Those authors suggested that the system was behaving as an unintentional‐isotachophoresis system under conditions aimed at carrying out zone electrophoresis.…”
Section: Resultssupporting
confidence: 90%
“…(i) The virus concentrations of two highly pure preparations (1.1 ± 0.1 and 3.9 ± 0.6 mg/mL virions, n = 3, respectively) as determined via CE 41 (exemplary electropherogram in Figure 2 b, top) were comparable to that of conventional preparations. 41 (ii) Upon incubation for 10 min at 56 °C in BGE, 47 CE resolved the four VPs and the viral RNA genome (exemplary electropherogram in Figure 2 b, bottom); the CE profiles of all four batches were again indistinguishable. (iii) The specific infectivity (TCID 50 /mL; 2.31 × 10 11 and 4.14 × 10 11 , respectively) was essentially the same for all four batches.…”
Section: Resultsmentioning
confidence: 99%
“…The intact virions were complexed to His 6 ‐tagged recombinant receptor fragments followed by binding to Ni 2+ presenting agarose beads. Upon application of spin SEC to this mixture, bound native 150S virions as well as free smaller proteins like VP4 (with 7.35 kDa, according to ) were separated from subviral assemblies (see Section ). The resulting fractions were checked by CE and the fraction showing the highest content of AI was subjected after addition of SDS to further heating.…”
Section: Resultsmentioning
confidence: 99%